WEB-BASED INFORMATION SYSTEMS FOR SERVICES IN THE SOCIAL DEPARTMENT OF PESAWARAN DISTRICT - Mita Oktaviana; Sri Karnila (Jurnal TAM (Technology Acceptance Model), 2020)
This study analyzed the services at the Social Service office of Pesawaran District that were previously conducted conventionally and did not yet have a special system. The results of the analysis was applied in providing services with optimal PMKS data collection, registration of Joint Business Groups (KUBE) and updating the activity in a web-based system facilitation, so that the Social Service Office of Pesawaran District can provide information services well. The development of this system used a prototype method starting from gathering needs: meeting developers and clients (social service provider) determining general objectives, and specifically describing the parts that were needed, design: designing aspects of this software is the basis for making prototypes using development support tools UML Unified Modeling Language system, Prototype evaluation: the client (social service provider) evaluates and tests prototypes that are created and used to clarify the needs of software users. this web-based system provides all the information to the services available and also the assistance available at the Pesawaran Social Service. With this system, it can provide optimal services that can be directly accessed by all communities in Pesawaran Regency. So that all available assistance can be given to the community quickly and accurately